Analisis Kinerja Realisasi Anggaran Pendapatan Dan Belanja Daerah Pemerintah Provinsi Bali Tahun 2019-2023 - Stephanus Andi Adityaputra; Yunisa Septi Yudhanti (Universitas Riau Kepulauan, 2025)
Abstract This study aims to evaluate the financial performance of the Bali Provincial Government through an analysis of the realization of the Regional Revenue and Expenditure Budget (APBD) for the period 2019 to 2023. This study was conducted using a quantitative descriptive method through the utilization of secondary data obtained from the official website of the Bali Provincial Government. The evaluation was carried out through the calculation of 6 financial indicators, namely: revenue budget variance, expenditure budget variance, regional financial independence ratio, expenditure efficiency ratio, regional financial dependency ratio, and decentralization degree ratio. The results of the study indicate that the achievement of financial performance in the analysis of revenue budget variance has not been able to exceed the revenue budget target, financial performance in the analysis of expenditure budget variance is good because regional spending can be managed well, the independence ratio has high criteria and has a delegative relationship pattern, the expenditure efficiency ratio shows fairly efficient criteria, the dependency ratio shows that it is still quite dependent on the central government, and the degree of decentralization shows very good criteria.. Keywords: financial performance, realization, budget, variance, ratio Abstrak Penelitian ini bertujuan mengevaluasi kinerja keuangan Pemerintah Provinsi Bali melalui analisis realisasi Anggaran Pendapatan dan Belanja Daerah (APBD) pada periode 2019 sampai dengan 2023. Penelitian ini dilakukan dengan menggunakan metode deskriptif kuantitatif melalui pemanfaatan data sekunder yang diperoleh dari website resmi Pemerintah Provinsi Bali. Evaluasi dilakukan melalui penghitungan 6 indikator keuangan, yakni: varians anggaran pendapatan, varians anggaran belanja, rasio kemandirian keuangan daerah, rasio efisiensi belanja, rasio ketergantungan keuangan daerah, dan rasio derajat desentralisasi. Hasil penelitian menunjukkan bahwa pencapaian kinerja keuangan pada analisis varians anggaran pendapatan belum dapat melampaui target anggaran pendapatan, kinerja keuangan pada analisis varians anggaran belanja termasuk baik karena belanja daerah dapat dikelola dengan baik, rasio kemandirian memiliki kriteria yang tinggi dan memiliki pola hubungan delegatif, rasio efisiensi belanja menunjukkan kriteria yang cukup efisien, rasio ketergantungan menunjukkan masih cukup bergantung pada pemerintah pusat, dan derajat desentralisasi menunjukkan kriteria yang sangat baik.. Keywords: kinerja keuangan, realisasi, anggaran, varians, rasio